Change in inorganic phosphate physical state can regulate transcription. Issue 4 (20th October 2019) - Gottesman, Max E.; Mustaev, Arkady
ABSTRACT: Inorganic phosphate (Pi ), a ubiquitous metabolite, is involved in all major biochemical pathways. We demonstrate that, in vitro, MgHPO4 (the intracellular Pi form) at physiological concentrations can exist in a metastable supersaturated dissolved state or as a precipitate. We have shown that in solution, MgHPO4 strongly stimulates exonuclease nascent transcript cleavage by RNA polymerase. We report here that MgHPO4 precipitate selectively and efficiently inhibits transcription initiation in vitro . In view of the MgHPO4 solubility and in vitro sensitivity of RNA synthesis to MgHPO4 precipitate, at physiological concentrations, MgHPO4 should cause a 50–98% inhibition of cellular RNA synthesis, thus exerting a strong regulatory action. The effects of Pi on transcription in vivo will, therefore, reflect the physical state of intracellular Pi .